Internalisasi Pendidikan Profetik dalam Pendidikan Islam - Munif, Moh. Vito Miftahul; Audah, Ali (Tarsib: Jurnal Program Studi PGMI, 2024)
Prophetic education is an educational method that takes inspiration from the teachings of the Prophet Muhammad Saw. where the principle is to prioritize integration. The process of education or transfer of knowledge in the field of knowledge must be based on what is in the Qur'an and As-Sunnah, so that the goals of the world and the hereafter can be achieved simultaneously through prophetic education, the purpose of this study is to describe the process of internalizing prophetic education. This research uses a descriptive qualitative approach in the form of library research. The analysis technique used is content analysis. The results of this study indicate that 1) Prophetic education is the process of transferring knowledge and prophetic values that aim to build morals, as well as getting closer to God and nature while understanding them to build an ideal social community (khoirul ummah), as well as the achievement of intellectual, emotional, and moral learners who can develop as a whole. 2) The internalization of prophetic education is carried out with 3 stages, namely the value transformation stage, the value transaction stage, and the transinternalization stage.